Drugfever: Case report - Siti Nurdjanah, Siti Nurdjanah (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1991)
Fever is a feature of a variety of infectious and non-infectious diseases. Recognition of drug fever in hospitalized patients is critical. If the condition is not appreciated, the patient may be subjected to prolonged hospitalization and a variety of unnecessary antibiotics, laboratory, and radiologic studies.Fever is considered to be drug-induced, -an incompletely understood allergic hypersensitivity reaction to medication-, if other causes can be eliminated, if the temperature elevation is temporally associated with the administration ofsensitizing medication, and if the fever disappears within 72 hours after discontinuation of the medication. Any drug has the capacity to induce fever as an adverse reaction.This article reported three cases of drug fever. Patients appeared "inap p ropria tely well for the magnitude. of their temperature elevation. They typically felt comfortable. Administration of antipyretic medications made the patients very uncomfortable and induced shaking chills. Their body temperature normalized within 24 hours after discontinuation of sensitizing medication in two patients. However, in one patient, the drug was not discontinued and the fever sustained, because she needed the drug.Key Words: drug fever - adverse reaction - allergy - hypersensitivity - antipyretics